2022
DOI: 10.1001/jamanetworkopen.2022.44922
|View full text |Cite
|
Sign up to set email alerts
|

Association of Recreational Cannabis Legalization With Cannabis Possession Arrest Rates in the US

Abstract: ImportanceRecreational cannabis legalization (RCL) has been advocated as a way to reduce the number of individuals interacting with the US criminal justice system; in theory, however, cannabis decriminalization can achieve this objective without generating the negative public health consequences associated with RCL. It is still unclear whether RCL can bring additional benefits in terms of reducing cannabis possession arrests in states that have already decriminalized cannabis.ObjectiveTo examine whether RCL wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As for the stigmatization concern of cannabis illegality for those who have been sent to the criminal justice system, civil liberties advocates support recreational marijuana decriminalization across states. According to a recent study, youth marijuana possession arrest rates are unchanged in marijuana decriminalization states [ 22 ]. From this evidence, we speculate that there is an urgent need of evaluating health and criminal justice outcomes in youths since the State of Nevada has a new legal establishment of cannabis consumption lounges.…”
Section: Discussionmentioning
confidence: 99%
“…As for the stigmatization concern of cannabis illegality for those who have been sent to the criminal justice system, civil liberties advocates support recreational marijuana decriminalization across states. According to a recent study, youth marijuana possession arrest rates are unchanged in marijuana decriminalization states [ 22 ]. From this evidence, we speculate that there is an urgent need of evaluating health and criminal justice outcomes in youths since the State of Nevada has a new legal establishment of cannabis consumption lounges.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies to date suggest a more nuanced picture. In the U.S. and Canada, recreational cannabis laws (RCLs) have been associated with reductions in total cannabis arrests and racialized arrest disparities measured on the absolute scale [7][8][9][10][11][12][13]. When measured on the relative scale, however, studies have found that racialized disparities commonly persist or even increase following law adoption, as the harms associated with cannabis enforcement continue to be disproportionately concentrated among racialized groups [8,9,11,14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Canada, annual sales of cannabis for non-medical purposes totaled $4.5 billion in 2022 [3]. Legalization has also had criminal justice system ramifications, leading to significant decreases in cannabis-related charges or arrests in Canada [4] and the U.S. [5]. However, the increased acceptance of cannabis use has led to greater prevalence of some hazardous behaviors.…”
Section: Introductionmentioning
confidence: 99%